Territory : new trajectories in law - Blomley, Nicholas K. (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"This book introduces readers to the concept of territory, as it applies to law, while demonstrating the particular work that territory does in organizing property relations. Territories can be found in all societies, and at all scales, although they take different forms. The concern here is on the use of territories in organizing legal relations. Law, as a form of power, often works through a variety of territorial strategies, serving multiple legal functions, such as attempts at creating forms of desired behaviour. Landed property, in Western society, is often highly territorial, reliant on sharply policed borders and spatial exclusion. But rather than thinking of territory as obvious and given, or as a natural phenomenon, this book focuses particularly on its relation to property to argue that territory is both a social product, and a specific technology, which organizes social relations. That is: territory is not simply an outcome of property relations, but a means by which such relations are enforced, naturalized, and contested; and here, it is seen as a strategic means through which property relations are communicated, enforced, contested, imagined and legitimized. Accessible to students, this book will be of interest to those working in the areas of sociolegal studies, geography, urban studies and politics"--
Territory -- Property -- Making the territory of property -- Racializing territory -- Fortifying territory -- Opening up territory.
OCLC-licensed vendor bibliographic record.
Keywords: Law and geography; LAW / Property; SOCIAL SCIENCE / Human Geography; LAW / Administrative Law & Regulatory Practice